Enhancing Student Authorship and Broadening Personal Latitude in the Mathematics Classroom With Rich Dialogic Discourse - Wing Kin Cheng (郑永健); Oi-Lam Ng (吴蔼蓝); Yujing Ni (倪玉菁) (ECNU Review of Education)
Purpose In this article, we explore how student authorship may be enhanced among learners in mathematics classrooms in a Hong Kong primary school through rich dialogue discourse. Design/Approach/Methods Using qualitative methods, that is, coding and discourse analysis, we examine the relationship between student authorship and personal latitude through a case study of two Grade 4 mathematics lessons taught by two primary mathematics teachers, respectively. Findings We discuss the study's findings in relation to how teachers can engage themselves and their students in dialogic discourse to offer student choices and opportunities and generate original voices. Originality/Value Personal latitude was found when the students were given the choice to use their original voices. The learners assumed the role of author; consequently, authorship was enhanced in ensuing rich dialogic discourse.